The role of chemotherapy in the modern management of melanoma. (November 2014) - Lee, Rebecca Jane; Ul-Ain-Tariq, Noor; Fusi, Alberto; Bowyer, Samantha; Lorigan, Paul
SUMMARY : The last 4 years have seen dramatic changes in the treatment of advanced melanoma, largely based on advances in targeted therapy and immunotherapy. This article examines the role of chemotherapy in the modern management of melanoma. We examine the evidence for promising new agents and discuss their position in the sequencing of treatment options for patients with advanced disease. In addition, we discuss the combination of chemotherapy with targeted treatments and immune therapies. Finally, we discuss future areas of research for ensuring that we maximize the potential of all agents available to us and identify new, effective treatments.